Fibrinogen and hemoglobin predict near future cardiovascular events in asymptomatic individuals - Moritz Lassé (Nature Portfolio, 2021)
Abstract To identify circulating proteins predictive of acute cardiovascular disease events in the general population, we performed a proteomic screen in plasma from asymptomatic individuals. A “Discovery cohort” of 25 individuals who subsequently incurred a cardiovascular event within 3 years (median age = 70 years, 80% male) was matched to 25 controls remaining event-free for > 5 years (median age = 72 years, 80% male). Plasma proteins were assessed by data independent acquisition mass spectrometry (DIA-MS). Associations with cardiovascular events were tested using Cox regression, adjusted for the New Zealand Cardiovascular Risk Score. Concentrations of leading protein candidates were subsequently measured with ELISAs in a larger (n = 151) independent subset. In the Discovery cohort, 76 plasma proteins were robustly quantified by DIA-MS, with 8 independently associated with cardiovascular events. These included (HR = hazard ratio [95% confidence interval] above vs below median): fibrinogen alpha chain (HR = 1.84 [1.19–2.84]); alpha-2-HS-glycoprotein (also called fetuin A) (HR = 1.86 [1.19–2.93]); clusterin isoform 2 (HR = 1.59 [1.06–2.38]); fibrinogen beta chain (HR = 1.55 [1.04–2.30]); hemoglobin subunit beta (HR = 1.49 [1.04–2.15]); complement component C9 (HR = 1.62 [1.01–2.59]), fibronectin isoform 3 (HR = 0.60 [0.37–0.99]); and lipopolysaccharide-binding protein (HR = 1.58 [1.00–2.49]). The proteins for which DIA-MS and ELISA data were correlated, fibrinogen and hemoglobin, were analyzed in an Extended cohort, with broader inclusion criteria and longer time to events, in which these two proteins were not associated with incident cardiovascular events. We have identified eight candidate proteins that may independently predict cardiovascular events occurring within three years in asymptomatic, low-to-moderate risk individuals, although these appear not to predict events beyond three years.